Media, Market Sentiment and Startups IPO: Study of Initial Return in Indonesia Stock Market - Meliana Meliana; Yunieta Anny Nainggolan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study seeks to investigate the impact of media and market sentiment on IPO initial returns in the Indonesian Stock Exchange from 2017 to 2022. With a prevalent occurrence of low IPO offering prices, initial price jumps on the first day of trading, and subsequent long-term price drops demands a robust explanation. While numerous studies have examined the impact of firm’s internal factors on IPO performance, these studies primarily concentrated on firm-level issues. By incorporating startups' dummy variable, we have placed particular emphasis on exploring the impact of the increasing number of startup firms' IPOs on the initial return. Given the increasing proliferation of IPOs among firms, our study aims to delve into their impact on initial returns by incorporating a dummy variable into our analysis, focusing on how these particular firms influence the initial return dynamics. Multiple linear regression analysis are used, with control variables namely pre-IPO financial performances, Underwriter reputation dummy and COVID-19 Year dummy. Results show the level of pre-IPO media coverage and herd behavior level have a significant effect on initial return, while 30 days pre-IPO market volatility negatively affects initial return. However, 30 days pre-IPO investor sentiment has a positive but non-significant impact. Additionally, the result reveals that the startup IPOs tend to have higher initial return, reflected by a positive and significant relationship with the initial return. Future research endeavours can expand the scope by conducting similar analyses across multiple countries, such as those within the ASEAN region or other developing nations with comparable characteristics in their capital markets to Indonesia. This broader approach would provide valuable insights into the IPO dynamics within a wider context